2021
DOI: 10.36399/gla.pubs.234936
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Risk-related Disclosures in Extractive Industries

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In developing this point, Tucker & Lowe (2014: 406) argued that "professional accounting bodies act as mediators between academia and practice ...". Indeed, recent examples of this dynamic related to our topic include Adams (2017Adams ( , 2020Adams et al, 2020) and Baboukardos et al (2021), all reports that have been published by professional accounting bodies. Furthermore, professional accounting bodies have worked collaboratively on these matters through the Accounting Bodies Network of the Prince of Wales' Accounting for Sustainability charity 3 .…”
Section: Introductionmentioning
confidence: 98%
“…In developing this point, Tucker & Lowe (2014: 406) argued that "professional accounting bodies act as mediators between academia and practice ...". Indeed, recent examples of this dynamic related to our topic include Adams (2017Adams ( , 2020Adams et al, 2020) and Baboukardos et al (2021), all reports that have been published by professional accounting bodies. Furthermore, professional accounting bodies have worked collaboratively on these matters through the Accounting Bodies Network of the Prince of Wales' Accounting for Sustainability charity 3 .…”
Section: Introductionmentioning
confidence: 98%
“…We do acknowledge, however, that these pressures are unlikely to be uniform across industries and sectors or even across firms. Prior research has shown that the amount of carbon information a firm discloses tends to correspond to their industry's carbon profile and the associated public perceptions to do 'what is right' (Comyns, 2016;Baboukardos et al, 2021a). Therefore, cognitive legitimacy may mean different industries to make different disclosures.…”
Section: Medar 323mentioning
confidence: 99%
“…That said, the empirical evidence on climate-related disclosures is somewhat limited (Baboukardos et al, 2021a(Baboukardos et al, , 2021b. Significant gaps exist in terms of the status quo reporting practices, the best practices firms should implement to fulfil their stakeholders' information needs and how firms might go about transitioning to a "net zero" carbon strategy (Scholten et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, firms disclose significant value through their reserves which are at risk of becoming 'stranded' or impaired due to steps taken to combat climate change. Baboukardos et al (2021) found that only 60 percent of firms in the extractive industries provide a reserves/resources statement, 10 percent include climate change risks in future cash flow estimations as part of impairment calculations, and no firms identify climate change risk as important in determining assets' useful lives. Besides indicating that firms need to do much more to recognise climate change risks in financial reporting, these results also signal prospective amendments to accounting standards such as IAS 36 (Impairment of Assets) and IAS 37 (Provisions, Contingent Liabilities and Contingent Assets).…”
Section: Introductionmentioning
confidence: 99%